Increasing Traffic Law Awareness Among Junior High School Students Through Community Service Activities Based on Legal Education - Jaudah, Tsuroyyaa Maitsaa'; Wirasti, Siti; Andini, Retno; Kusnaneni, Tyas (Borobudur Journal on Legal Services, 2025)
Traffic violations involving students, particularly those still in junior high school (SMP), are still frequently encountered in the field. Low legal awareness and a lack of understanding of the importance of traffic discipline are the main factors triggering this condition. This community service activity aims to provide a real contribution from law intern students in developing a character of orderly traffic from an early age through an educational and preventive approach. The strategies used include legal counseling on traffic regulations, as well as fostering awareness of traffic discipline tailored to the characteristics of junior high school students. The community service method used is lectures and discussions that actively involve students in discussions and questions and answers regarding traffic rules and ethics. The activity was carried out directly in Tempak Village, Candimulyo District, Magelang Regency, with the support of local residents and parents of junior high school students. The results of the activity showed an increase in students' understanding of traffic regulations, awareness of the importance of road safety, and changes in attitudes towards being more disciplined and responsible. In conclusion, the role of law intern students has been proven to make a positive contribution in instilling the values of orderly traffic from an early age as part of the character formation of a law- conscious young generation.